المرأة في شعر الخوارج - صالح, إبراهيم حسن (مجلة جامعة تكريت للعلوم الإنسانية, 2009)
أساليب التوكيد في شعر الخوارج
Keywords: Poésie kharijite

السرد في كتاب "الكامل في اللغة والأدب" أخبار الخوارج مثالاً - عبيد, عباس (مجلة آداب المستنصرية, 2009)
إن الأخبار الواردة في مثل الغرباء تشترك جميعها في مغزى أن قضبان القياس في التفكير في أسس المنطق الفريد لسيطرة رؤية واحدة ومصادرة الرأي الآخر ، إبن السيد أبو علي الفارسي ، سموا بالهره لأن هم الهواء والغضب…
Keywords: Kharijisme

التفسير المنحرف والباطني عند الخوارج - محمد, شهاب احمد (مجلة كلية التربية الأساسية, 2009)
لحمد الله رب العالمين ، والصلاة والسلام على سيد المرسلين ، سيدنا محمد وعلى أله وصحبه أجمعين : وبعد فأن التفسير عند الفرق الإسلاميّة يحظى باهتمام الباحثين والدارسين لا سيما إذا كانت هذه الفرقة المراد التعريف…
Keywords: Kharijisme

التحول الديمقراطي في سلطنة عمان: الواقع والتحديات وآفاق المستقبل - بني سلامة, محمد تركي (مجلة دراسات الخليج والجزيرة العربية, 2009)
تهدف هذه الدراسة إلى إلقاء الضوء على واقع التجربة الديمقراطية في سلطنة عُمان، عبر تعريف المفاهيم الأساسية في الدراسة، وتطورها التاريخي، ولا سيما بعد انطلاق الموجة الثالثة للتحول الديمقراطي في العالم، ثُم تتناول مفهوم الديمقراطية، وأنواعها، والمتطلبات التي لا بد من توافرها في نظام سياسي حتى يمكن اعتباره ديمقراطياً. ثم تتناول التحول الديمقراطي في سلطنة عُمان، الذي هو في حقيقته ناتج من رغبة صانع القرار في تبني الخيار الديمقراطي أسلوباً في الحكم أكثر منه تكتيكاً لمواجهة بعض المشكلات، ولا سيما الاقتصادية، بعد تراجع إنتاج النفط والغاز. وقد تناولت الدراسة عمق الإصلاحات السياسية التي تم اتخاذها، وخصائص التجربة العمانية، حيث أكدت دور المؤسسات السياسية - وفي مقدمتها الأحزاب السياسية، والثقافة الديمقراطية - في تسريع عملية التحول الديمقراطي، وعرضت لأبرز المعوقات والتحديات السياسية والاقتصادية التي تبطئ عملية التحول الديمقراطي. وأخيراً، تم استشراف مستقبل التجربة الديمقراطية في سلطنة عُمان، في ضوء الضغوط المحلية والدولية والإقليمية، وقد خلصت الدراسة إلى أن التجربة الديمقراطية في سلطنة عُمان هي تجربة رائدة، وقابلة لمزيد من التطور والتقدم.

الجاليات العربية الإسلامية المبكرة في غرب أفريقيا وأثرها في نشر الإسلام واللغة العربية - الدهماني, الدهماني سالم (المجلة العلمية بكلية الآداب, 2009)
Keywords: Invasion arabe -- Afrique du Nord

أحمد بن سليمان بن النظر السمائلي : عصره - سيرته - ما وصل إلينا من آثاره - السليمي, محمود بن مبارك بن حبيب (مجلة دراسات تاريخية, 2009)

الأباضية في ضوء الكتاب والسنة - سليمان, أسامة بن علي (التوحيد, 2009)

الإصرار على الذنب وأثره فى العمل عند الإباضية - وينتن, مصطفى بن الناصر (مجلة جامعة الأمير عبد القادر للعلوم الإسلامية, 2009)

الهجرة الهلالية و أثرها في تغيير البنية الاجتماعية لبلاد الزاب - عمارة, علاوة (مجلة الآداب و العلوم الإنسانية, 2009)
لقد قدمت الدراسات الكلاسيكية عدة تفسيرات لتاريخ المغرب الوسيط ربطته في أغلبها بدور الكيانات السياسية التى تأسست في مناطق الشمال في تحديد مصاره . غير أن الاهتمام سرعان ما انتقل إلى مناطقه الجنوبية المشتهرة بثقافته الواحية في محاولة لدراسة تاريخ العنصر الإباضي المستقر أساسا بمدن ميزاب و بجبل نفوسة .

الإباضية والمعتزلة في عهد الدولة الرستمية - أبو عمران, الشيخ (الدراسات الإسلامية, 2009)
بدون ملخص

دراسة وثيقة تاريخية للإمام أفلح بن عبد الوهاب الرستمي بعنوان: " النصيحة العامة من الإمام أفلح بن عبد الوهاب إلى كل من كان تحت لوائه من المسلمين" - بوركبة, محمد (المجلة الجزائرية للمخطوطات, 2009)
مؤلف هذه الوثيقة، هو أفلح بن عبد الوهاب بن عبد الرحمن بن رستم، ثالث أئمة الدولة الرستمية الإباضية، بويع بالإمامة بعد وفاة والده عبد الوهاب (198-247ﻫ/814-861م)، واتبع نهج أبيه عبد الوهاب بن عبد الرحمن في تسيير شؤون الدولة الرستمية، وعدل بين الرعية بالحق. وكان تقيـا وورعا، مما دفع الإباضيين في المجتمع الرستمي إلى التمسك به إماما وحاكما عليهم. عنى الإمام أفلح بن عبد الوهاب بنشر الأمن والسلم في ربوع الدولة فتطورت الحضارة الإباضية الرستمية في عهده ووصلت إلى ذروتها من العز والتقدم، حيث بنى الأغنياء القصور الفخمة واتخذت الضياع الواسعة، وكثر العبيد والحشم، واتسع نطاق التجارة اتساعا واسعـا من المشرق الإسلامـي إلى السودان.
Keywords: Dynastie rustumide

التأريخ والموسوعية عند علماء الإباضية -الوارجلاني والمُصعبي والقُطب أطفيَّش أنموذجا- - حاج أمحمد, يحيى بن بهون (مجلة الواحات للبحوث والدراسات, 2009)
التأريخ والموسوعية عند علماء الإباضية -الوارجلاني والمُصعبي والقُطب أطفيَّش أنموذجا-

Orientalism and relationships between Islam and The West - Salimi, Abdulrahman al- (Krakowskie Studia Międzynarodowe, 2009)
"Since the end of the Second World War, a dispute has continued amongst Muslims and Arabs regarding the character of Orientalism. The period during the Cold War played a principal role in the shaping of disparate views when some of the key Arab states leaned towards the former Soviet Union, while others aligned themselves with the United States and its allies. Such alignments resulted in distinctive orientations towards cultural studies that found expression in a ‘soft’ confrontation led by Islamists on one side and leftwing leaders on the other. In exploring these differences, it is important to begin by defining what is meant by Orientalism. To do this, one needs to examine the three main areas of scholarly focus in the last two hundred years: the editing of Arabic manuscripts, historical scholarship on Islam, and Islamic religious studies and its associated branches."(...)

«أهلُ الله وخاصَّتُه»؛ المستظهرون لكتاب الله العزيز بالقرارة (الحياة, 2009)

أهمية توثيق عقد الزواج، ومخاطر الزواج العرفي على الأسرة والمجتمع - أبو بكر, صالح بن عبد الله (الحياة, 2009)
Keywords: Droit coutumier -- Mzab

الأطعمة الـمُصنَّعة الحديثة، بين التأصيل الشرعي والتحليل العلمي - أرفيس, أحمد بن محمد (الحياة, 2009)

تحية لوادي ميزاب - السيابي, عبد الله بن راشد (الحياة, 2009)

مدلول كلمة "حرب" في القرآن الكريم - الشيخ بالحاج, عيسى بن محمد (الحياة, 2009)

قراءة في رسالة مهرجان الوفاء - الشيخ بالحاج, قاسم بن أحمد (الحياة, 2009)

محطات في تاريخ بلدة القرارة (الحلقة الأولى: زمن التأسيس) - الشيخ بالحاج, قاسم بن أحمد (الحياة, 2009)

خصائص تفسير الشيخ إبراهيم بن عمر بيوض - الوزناجي, نادية (الحياة, 2009)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

البعد العقدي والحضاري للفن (قراءة تحليلية في فكر بيجوفيتش ومالك بن نبي) - بابا عمي, محمد بن موسى (الحياة, 2009)

تحية الجزائر لسلطنة عمان - باجو, صالح بن إبراهيم (الحياة, 2009)

القضايا الوطنية والعربية والإسلامية من منظور أعلام ميزاب (1902-1962) - بن عمر, موسى بن بكير (الحياة, 2009)
Keywords: Biographies -- Mzab -- 20e siècle

الافتتاحية - بن يحيى, يحيى بن صالح (الحياة, 2009)

المضمون الإسلامي في الشعر الجزائري الحديث - بوحجام, محمد بن قاسم ناصر (الحياة, 2009)
Keywords: Poésie -- Mzab

محمد عاشق السواد…! (نثر) - بوحجام, محمد بن قاسم ناصر (الحياة, 2009)

الحماية القانونية المتميِّزة للأملاك الوقفية في الجزائر - بوراس, عيسى بن محمد (الحياة, 2009)
Keywords: Waqf (fondations) -- Mzab

في الذكرى العشرين لرحيل شيخ الشباب وشاب الشيوخ (الشيخ إبراهيم قرادي) - حاج أمحمد, يحيى بن بهون (الحياة, 2009)

فصل في الفصل بين عبد الله بن إباض الحيادي والمحكمة ... (الحلقة الأولى) - حريزي, موسى بن إبراهيم (الحياة, 2009)

فقه المال العام عند الإباضية (الحلقة الثالثة: عند فقهاء إباضية المشرق) - حمدي, محمد بن صالح (الحياة, 2009)
Keywords: Fiqh

مقياس "علم الاجتماع الإسلامي" في الجامعة الجزائرية .... - خواجة, عبد العزيز بن محمد (الحياة, 2009)

التعليم القرآني في الزوايا والمدارس القرآنية بين الواقع والمأمول... - دفرور, رابح (الحياة, 2009)
Keywords: Enseignement -- Mzab

اعتراف بالمقام - زيد الخير, مبروك (الحياة, 2009)

خطاب الشيخ إبراهيم بن عمر بيوض في مؤتمر قدماء التلاميذ بغرداية (مؤرخ بـ 29/11/1373 - 29/07/1954) - شريفي, سعيد بن بالحاج (الحياة, 2009)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

قراءة سوسيو-أخلاقية لمنظومة قيم التدريس - مرموري, بشير بن عمر (الحياة, 2009)
Keywords: Enseignement -- Mzab

إصلاح الأنفس بالقرآن وليس بتغيير الإنسان - ناصر, محمد صالح (الحياة, 2009)
Keywords: Développement personnel -- Aspect religieux

Review of In the Shadow of the Ancestors. The Prehistoric Foundations of the Early Arabian Civilization in Oman - Lombard, Pierre (Paléorient, 2009)
Keywords: Recension

Jeffrey T. Kenney, Muslim Rebels: Kharijites and the Politics of Extremism in Egypt (Oxford: Oxford University Press, 2006). Pp. 234. $45.00 cloth. - Kalmbach, Hilary (International Journal of Middle East Studies, 2009)
Keywords: Recension

Bernardie-Tahir, Nathalie (dir.) (2008) L’autre Zanzibar. Géographie d’une contre-insularité. Paris, Karthala, 379 p. (ISBN 978-2-84586-946-2) - Bouchard, Christian (Cahiers de géographie du Québec, 2009)
Un article de la revue Cahiers de géographie du Québec, diffusée par la plateforme Érudit.
Keywords: Recension

علاقة الرستميين بالإمارة الأموية في الأندلس - بوباية, عبد القادر (التراث العربي, 2009)
Keywords: Relations -- Tahert -- Andalousie

قيام نظام الإمامة في عمان (1331 - 1339هـ / 1913 - 1920م) - التركي, عبد الله بن إبراهيم (مجلة جامعة أم القرى لعلوم الشريعة والدراسات الاسلامية, 2009)
يهدف هذا البحث إلى دراسة عودة نظام الإمامة في عمان، وظهوره كقوة منافسة للسلطان العماني، ومناوأة للنفوذ البريطاني في المنطقة. \ فمنذ توقيع معاهدة الحماية بين سلطنة عمان وحكومة الهند البريطانية عام 1308 هـ/1891 م تحولت العلاقة بين الجانبين إلى حكم غير مباشر من قبل بريطانيا لعمان، عبر الوكيل السياسي والقنصل البريطاني في مسقط، فتم منع تجارة الرقيق وتجارة السلاح. وتحت ذريعة مقاومة تلك التجارتين، تم تضييق الخناق علي القبائل العمانية وتم تدمير كثير من سفنها التجارية، وفي المقابل تم منح الرعايا البريطانيين مزيداً من الحرية والمميزات. \ أدت تلك الإجراءات إلى تجمع القبائل العمانية ومعظمها من القبائل الأباضية. وتم انتخاب إمام من بينهم وذلك عام 1331هـ/ 1913م، وتشكلت حكومة محلية داخل عمان، ونقضت هذه القبائل بيعتها للسلطان، وأنشأت قوة عسكرية استطاعت أن تستولي بها علي معظم المناطق العمانية سوى بعض الموانئ المهمة مثل: مسقط، ومطرح. \ ومن هنا تدخلت بريطانيا إلى جانب السلطان فيصل بن تركي ثم إلى جانب ابنه تيمور بن فيصل وذلك بالدعم المادي والعسكري، ثم تدخلت بوساطة بين الإمام والسلطان وعقدت عدة لقاءات بين الجانبين أسفرت عن توقيع اتفاقية السيب عام 1339 هـ/ 1920م وبموجب ذلك انقسمت عمان، ففي الداخل يحكم الإمام، وفي الساحل يحكم السلطان. \ يهدف هذا البحث * إلى دراسة عودة نظام الإمامة (1) في عمان وظهوره كقوة منافسة للسلطان العماني ومناوأة للنفوذ البريطاني في المنطقة، ومحاولة تلمس الأسباب التي أدت إلى نجاحه كقوة داخلية استطاعت أن تستقطب عدداً كبيراً من القبائل العمانية وذلك في العقد الرابع من القرن الرابع عشر الهجري، العقد الثاني من القرن العشرين الميلادي، ثم تتبع مراحل نزاع الإمامة مع السلطان العماني حتى تم توقيع اتفاقية السيب (2) عام 1339 هـ/ 1920 م بين السلطنة العمانية والإمامة الأباضية (3) بوساطة بريطانية، والجديد الذي تضيفه هذه الدراسة أنها تعتمد علي وثائق عربية وإنجليزية جديدة من أرشيف وزارة الهند في لندن، إضافة إلى عدد من المصادر العربية والأجنبية الأخرى \
Keywords: Vie politique -- Oman -- 1913-1932

Mediterranean islands in Tabula Peutingeriana - Pazarli, Maria (e-Perimetron, 2009)
Keywords: Cartes -- Djerba

The Iron Age ceramic tradition in the Gulf: a re-evaluation from the Omani perspective - Iamoni, Marco (Proceedings of the Seminar for Arabian Studies, 2009)
Keywords: Archéologie -- Oman

Rituals of Royalty and the Elaboration of Ceremony in Oman: View from the Edge - Chatty, Dawn (International Journal of Middle East Studies, 2009)

Retention of the passive verb in a Bedouin dialect of northern Oman - Eades, Domenyk (Zeitschrift Für Arabische Linguistik, 2009)
The present contribution examines the form and function of the apophonic ("internal") passive (AP) in an Arabic dialect of northern Oman. The AP is one of several features common to all the dialects of Oman, having been retained in dialects of both the "Bedouin" (B) and "sedentary" (S) types. In a study of the AP in dialects of Oman and eastern Arabia, Clive Holes (1998) showed that this category survives as a functioning marker of the passive voice in Omani S dialects mostly in the historically isolated interior of the country, albeit in verbs belonging to a restricted set of syntactic and lexicosemantic categories. The purpose of the present study is to determine whether the same process of recession has taken place in a B dialect of the Omani interior. Results of the study reveal that in the B dialect of the Hidyīwī tribe, whose dīra is located in the hinterland of Muḍaybi in northern Oman, the AP is significantly more productive than in the S dialects described by Holes. This contrast corresponds with certain socio-historical factors which distinguish the different speech communities of the interior. In particular, the Hidyīwī community is significantly more isolated from outsider contact and maintains a more homogeneous, tight-knit social structure than towns in which the S dialects are spoken.
Keywords: Linguistique -- Oman

العلاقات العمانية الفرنسية (1741-1810)م - عمر, باسمة عبد العزيز (مجلة الخليج العربي, 2009)
During the eighteenth century, the Arabian Gulf region had witnessed a great European competition and, due to its strategic location on the way to India, sultanate of Oman had felt such competition between England and France to have its ally and to be preferred, and due to the increase of such competition between England and France, Muscat thought that it is preferable to be idle in its relation with the two competitive powers at that time. In spite of that, the first roller of Albu-Said family, Ahmed bin Said (1741-1783) knew the benefit of the French friendship, the relation between Muscat and France had not developed to the level of diplomatic one but only a trade relation because England was competing them. However Muscat relations with France took a developed phase with Sultan bin Ahmed while he was rolling Muscat. He got benefit from the English - French competition to build a good relation with France in 1796, in addition to the predominant trade relations. Such action had its influence on England, which forced the Sultan to sign an agreement on 1800, rejecting some of the facilities which had been given to France before, and the English occupation of Morrishious Island (the main French Colony in the Indian Ocean), ended the French dreams in extending their power and finished a phase of a hesitated Omani-French relations.
Keywords: Relations -- Oman -- France

Le négoce de matières premières de Zanzibar et les affaires commerciales des négociants Kutchs et Occidentaux - Goswami, Chhaya (Synergies Inde, 2009)
Au dix-neuvième siècle, l’île de Zanzibar connut une intense activité commerciale (esclavage, ivoire, clous de girofle, tabac, noix de coco…). L’article montre la concurrence entre principales nations : France, Angleterre, Allemagne, Etats-Unis et Inde et montre comment cette dernière s’empara progressivement du marché.
Keywords: Zanzibar

Un’altra Storia. Le Memorie di Mohamed Fekini, patriota libico - Greppi, Carlo (I Sentieri della Ricerca, 2009)

L'art comme réappropriation du monde - Attia, Kader; Boulbina, Seloua Luste (Cahiers Sens public, 2009)
Keywords: Urbanisme -- Mzab

Life after Oil: Economic Alternatives for the Arab Gulf States - Peterson, John E. (Mediterranean Quarterly, 2009)
Keywords: Vie politique -- Oman -- 1970-2020

Mirroring Modernity: on consumerism in cosmopolitan Zanzibar - Prestholdt, Jeremy (Transforming Cultures eJournal, 2009)
This essay develops an image of nineteenth century Zanzibari consumer sensibilities by demonstrating how goods from and new engagements with distant locales affected the socio-cultural landscape of Zanzibar. The East African port’s particular cosmopolitanism represents one form of social reconstitution stimulated by global integration. It also represents a material vision of global relations that was discounted by nineteenth century theorizations of Western modernity. By focusing on the rise of a new materiality in Zanzibar, I excavate precolonial visions of global relations and cultural assimilations of global symbols. I argue that East African desires for goods produced all over the globe represented not simply a Westernization, Indicization, or Arabization of Zanzibar, but also a reconfiguration of a standardized set of global materials in an attempt to bring Zanzibari cultural forms into conversation with broader global trends.
Keywords: Zanzibar

Bir İbadî Çocuk İlmihali “Telkînü's-Sıbyan" - Ateş, Orhan (e-Makalat Mezhep Araştırmaları Dergisi, 2009)
Bir mezhebin fikirlerinin doğru anlaşılmasında kendi kaynakları oldukça önemlidir. İbâdîler'in itikadi görüşleri hakkında az sayıda çalışma yapılmış olmakla beraber İbâdî ilmihali hakkında ülkemizde herhangi bir çalışma mevcut değildir. Bu açıdan makaleye konu olan Telkinü's-Sıbyân isimli ilmihali önemsemekteyiz. Telkinü's-Sıbyân İbâdîler arasında tanınan bir kaynaktır ve Umman'da yaz tatillerinde İbâdî çocuklar bu kitabı okumaktadır. İlk kısmı İbâdî itikadı diğer bölümler ise ibadetlere ayrılmıştır. Bu sayede İbâdî itikadını ve namaz konusundaki farklı uygulamalarını kendi kaynaklarından öğrenmiş olacağız

Caractérisation génétique des isolats berbérophones du Sud tunisien par confrontation des résultats de trois marqueurs polymorphes - Fadhlaoui-Zid, Karima; Sanchez-Mazas, Alicia; Buhler, Stéphane; Khodjet-Elkhil, Houssein; Ben Amor, Mohamed; Comas, David; Dugoujon, Jean-Michel; Slama, Hmida; Benammar Elgaaied, Amel (Antropo, 2009)
In this study, we are interested to polymorphism of three genetic markers (GM Allotypes, HLA Classe II and mtDNA) in three Berber isolates (Chenini-Douiret, Matmata and Sened) localed in the South of Tunisia. Our objective is to evaluate the genetic impact of the invasions which Tunisia has knew after the Berber settlement by considering genetic diversity of these three isolates and by comparing these Berber populations to other North-African populations.
Keywords: Génétique -- Afrique du Nord

التنافس البريطانى الفرنسى للسيطرة على عمان 1888-1904: دراسة وثائقية - الأسدي, رياض جاسم محمد (الوثيقة, 2009)
Keywords: Vie politique -- Oman -- 1888–1913

Irregular Forces in Counterinsurgency Warfare - Clegg, Will (Security Challenges, 2009)
Keywords: Dhofar

Oman and the Franco-British Colonial Rivalry: The Bandar al-Jissah Crisis 1898-1900 - Ghailany, Yusuf A. M. al- (مجلة آداب, 2009)
Keywords: Vie politique -- Oman -- 1888–1913

التعليم في سلطنة عمان في ظل الخطة الخمسيت الثانية 1985-1981 - ياسين, سبلة طلال (دراسات تاريخية, 2009)
Keywords: Enseignement -- Oman

Etude expérimentale du trouble atmosphérique sur le site de Ghardaïa - Benkaciali, S.; Gairaa, K. (Revue des Energies Renouvelables, 2009)
Ce travail présente une étude qualitative et quantitative du trouble atmosphérique au site de Ghardaïa. Il s’agit de la détermination du facteur de trouble de Linke T*L, à partir des mesures instantanées données par une station radio métrique, qui utilise un système de poursuite à trois dimensions. Les mesures effectuées ont permis de déterminer ce coefficient, et de prédire sa variation annuelle et mensuelle qui présente un maximum au moi d’août (l’absorption par la vapeur d’eau est importante et une faible diffusion par les aérosols) et aussi une valeur importante du trouble au mois de juin (forte diffusion par les grains de sables), et un minimum en hiver (faible absorption par la vapeur d’eau et faible diffusion par les aérosols), à l’exception d’une période courte des tempêtes de sable (entre Mars et Mai) où la diffusion des aérosols grain de sable est prépondérante. D’après notre étude et nos observations sur site, on a constaté qu’il y a deux saisons principales à Ghardaïa (chevauchement des deux saisons).

The early Kharijites and their understanding of Jihad - Lahoud, Nelly (Mélanges de l’Université Saint-Joseph, 2009)
Keywords: Kharijisme

The Latest on the Archaeology of Southern Oman - Zarins, Juris (Journal of the American Oriental Society, 2009)
Keywords: Archéologie -- Oman

The Hawari of Socotra, Yemen - van Rensburg, Julian Jansen (The International Journal of Nautical Archaeology, 2009)
Haw ̄ar ̄ı are traditionally logboats carved from a single tree into a double-ended vessel which can be propelled by either sails or paddle. Haw ̄ar ̄ı can be found throughout the Indian Ocean from India through to East Africa, yet little is known about this ubiquitous vessel. The aims of this research are to address this lacuna in our knowledge by documenting the rich source of haw ̄ar ̄ı present on the island of Socotra, Yemen.
Keywords: Archéologie -- Oman

Les lieux de la revitalisation du judaïsme aujourd’hui. Vers un brouillage des frontières entre ashkénazes et séfarades ? - Endelstein, Lucine (Archives Juives, 2009)
Keywords: Judaïsme -- Djerba

De Tunis, à Djerba, confiscations et pillages - Danan, Ariel (Les Cahiers du judaïsme, 2009)
Keywords: Judaïsme -- Djerba

Review : Hoffmann-Ruf, Michaela: Scheich Muhsin bin Zahrän al-'Abri. Tribale Macht im Oman des 19. Jahrhunderts. Berlin (Klaus Schwarz) 2008. 46 Euro. ISBN 978-3-97997-353-8. - Lohlker, Rüdiger (Wiener Zeitschrift für die Kunde des Morgenlandes, 2009)
Keywords: Recension

Tourismus der Rückkehr als kulturelle Reserve: jüdische Pilger aus Frankreich auf dem Weg nach Djerba und zurück - Peveling, Barbara (Zeitschrift für Ethnologie, 2009)
JewishpilgrimsareyearlyvisitingtheGhriba Synagogueon the islandofDjerba in spring time. This pilgrimage offers for the social Jewish actors an opportunity to revitalize their oriental iden tity,which has been trailed away as consequence of theirmigration to Europe. For the local Muslims in Djerba the Jewish pilgrims renew the memories of the past local Jewish community. The touristic rite means a local resistance in the global interpretation of Jewish-Muslim relations, overshadowed by the Palestinian Conflict.
Keywords: Judaïsme -- Djerba; Tourisme -- Djerba

Review : Traditional Arts in Southern Arabia: Music and Society in Sohar, Sultanate of Oman - Urkevich, Lisa (The World of Music, 2009)
Keywords: Recension

Lemmes en berbère ancien provenant d’un glossaire berbéro-arabe et d’une œuvre ibâḍite-berbère médiévale - Ould-Braham, Ouahmi (Études et Documents Berbères, 2009)
Keywords: Linguistique

The Wajīhids of Oman - Salimi, Abdulrahman al- (Proceedings of the Seminar for Arabian Studies, 2009)
The downfall of the first Omani imamate in 280/885 represented the beginning of clashes between Ibāḍī ideology and the emerging family dynasties in different Omani provinces. The dynastic rulers sought to abolish the imamate system in the country, which led to serious conflict between distinguished political families and Ibāḍī scholars. Perhaps Wajīhid's reign in the fourth/tenth century symbolizes this best. This important family's rule of the country brought about fundamental changes in the areas of politics and commerce, which in turn has occupied the interest of many historians and archaeologists. This paper focuses on the emergence of the Wajīhid, their relations with Omani Ibāḍīs, and the subsequent political and economical changes in Oman. Finally, the paper examines this development in relation to the centre of the caliphate in Baghdad, the Būyids and Qarmatians (Carmathians).
Keywords: Archéologie -- Oman

الخوارج واراؤهم الإقتصادية (مجلة كلية التربية, 2009)
Keywords: Kharijisme

الرثاء بين الشيعة والخوارج في العصر الأموي - القتم, عبد الله (المجلة العربية للعلوم الإنسانية, 2009)
Keywords: Kharijisme

الكتابة التاريخية عند الخوارج في بلاد المغرب في القرنين الرابع والخامس الهجري - حسن, آمال محمد; شكيران, محمد عبدالكريم (صحيفة دار العلوم للغة العربية وآدابها والدراسات الإسلامية, 2009)
Keywords: Kharijisme

The Coinage of Obayda b. Al-Muhager Amir Al-Mu minin Al-khawarej in Iraq 256H 870 AD - Ramdan, Atef Mansour M. (أدوماتو, 2009)
عبيدة بن المهاجر من أتباع مساور الخارجي الذي ثار بالموصل ضد الخلافة العباسية. وقد حدث خلاف في عقيدة الخوارج بين مساور وعبيدة، واقتتلا بسبب ذلك، وانتهي الأمر بمقتل عبيدة على يد مساور. ولم تذكر المصادر التاريخية معلومات كافية عن هذه الحادثة، ولكن النقود- التي تعد مصدراً مهماً من مصادر التاريخ الإسلامي- ألقت الضوء عليها، من خلال درهمين نادرين باسم عبيدة ضرب نصيبين سنة 206ه، لم يسبق نشرهما أو دراستهما من قبل. وهما النموذجان الوحيدان المعروفان على مستوي العالم لهذا الخارجي؛ الأول محفوظ بمركز المسكوكات الإسلامية بجامعة توبنجن بألمانيا، والثاني كان ضمن مجموعة الدكتور اليش لوتز بألمانيا، ثم انتقل إلى ملكية جمعية النميات الأمريكية بنيويورك سنة 1987م.
Keywords: Numismatique -- Irak

Réflexions sur la révolte des berbères kharijites au Maghreb sous le gouvernement de Umar b. Hafs (151-154 / 768-771) une relecture des sources textuelles à la lumière des source numismatiques - Fenina, Abdelhamid (المجلة التونسية للعلوم الاجتماعية, 2009)
La révolte des Berbères kharijites sous le gouvernement de cUmar b. Hafs (151-154/768-771), objet de la présente étude, est relativement bien connue dans l’historiographie de l’Ifrîqiya. Toutefois, nous observons que les récits de nos chroniqueurs, dont aucun n’est contemporain des faits relatés, fourmillent d’informations tantôt confuses tantôt contradictoires. De fait, la chronologie de la révolte et certains autres faits historiques restent encore difficiles à discerner. Afin de contribuer à une meilleure connaissance de cet épisode obscur de l’histoire du Maghreb au milieu du IIe /VIIIe siècle, nous avons essayé de confronter les données recueillies dans nos sources textuelles aux témoignages numismatiques, contemporains des faits. Cette approche, nous a permis de proposer à la fois une relecture de certains faits rapportés par nos sources narratives et une chronologie de la révolte.
Keywords: Numismatique

مسند الربيع بن حبيب الإباضي : دراسة نقدية - آل حميد, سعد بن عبدالله بن عبدالعزيز (مجلة جامعة أم القرى لعلوم الشريعة والدراسات الاسلامية, 2009)
الإباضية إحدى الفرق الإسلامية التي كانت تعتمد في استدلالها من السنة على كتب الحديث المعروفة عند أهل السنة، ولم يكن يعرف لهم كتاب في الحديث إلا في القرون المتأخرة ؛ حين ظهر لهم كتاب " الجامع الصحيح ؛ مسند الربيع بن حبيب " الذي يقولون: إنه أصح الكتب بعد القرآن. ولكن هذا الكتاب لا يصح؛ لعدة أسباب، منها: ا) أنه ليس له أصل خطي يوثق به. 2) جهالة مرتبه الوارجلاني، وليس للكتاب إسناد إلى الوارجلاني، ولا بين الوارجلاني والربيع بن حبيب. 3) جهالة الربيع بن حبيب، وشيخه أبي عبيدة مسلم بن أبي كريمة 4) الانقطاع بين أبي عبيدة وجابر بن زيد؛ لعدم الدليل على تتلمذ أبي عبيدة على جابر بن زيد. 5) وجود الانقطاع والانقطاع الشديد في كثير من أسانيد الكتاب العليا؛ من الربيع فمن فوقه. 6) لم يظهر الكتاب في عصر الرواية والنقد، ولم يستدل الإباضية القدامى بأحاديثه فيما يعتقدونه مما يخالفون فيه غيرهم. 7) اعتذر متأخرو الإباضية عن عدم ظهور الكتاب لعلماء الحديث ؛ بالخوف من بطش الحكومات، فاعترض عليه بوجود فرصة لظهوره وقت قيام الدولة الرستمية الإباضية التي حكمت أكثر من ثلاثين ومئة سنة. 8) تفرد هذا الكتاب بأحاديث تضمنت أحكاما شرعية تحتاجها الأمة، ويحرص على معرفتها علماء الحديث، فلو كانت مرونة آنذاك لما غابت معرفتها عن علماء الحديث، بالإضافة لعدد آخر من الأحاديث المعارضة لأحاديث صحيحة، والله أعلم \
Keywords: Hadith -- Exégèse

الاستدلال على قضايا العقيدة عند ناصر بن أبي نبهان الخروصي (ت 1262 ھ/ 1846 م) - الحجري, سلطان بن عبيد (التفاهم, 2009)

المذهب الذَرّي الكلامي عند أبي بكر الكندي العُماني - المعمري, عبد الله (التفاهم, 2009)

Rabah NABLI, Les Entrepreneurs tunisiens. La difficile émergence d’un nouvel acteur - Ferréol, Gilles (Revue européenne des migrations internationales, 2009)
Keywords: Recension

Themes of the Ibadi/Omani Siyar - Salimi, Abdulrahman al- (Journal of Semitic Studies, 2009)
Keywords: Prosopographie -- Oman

PREVOST, V .- L'aventure ibadite dans le Sud tunisien (VIIle-xrne siècle). Effervescence d'une région méconnue. - Custers, Martin H. (Bibliotheca Orientalis, 2009)
Keywords: Recension

CUSTERS, M. H.- Ibadi publishing activities in the East and in the West c. 1880-1960s. An attempt to an inventory, with references to related recent publications - Sadgrove, Philip C. (Bibliotheca Orientalis, 2009)
Keywords: Recension

CUSTERS, M. H.- Al-Ibadiyya. A bibliography. Volume 1: Ibadis of the Mashriq; Volume 2: Ibadïs of the Maghrib (incl. Egypt); Volume 3: Secondary literature - Sadgrove, Philip C. (Bibliotheca Orientalis, 2009)
Keywords: Recension

Cohen-Tannoudji Denis (dir.), Entre orient et occident, Juifs et Musulmans en Tunisie, Paris, Éditions de l’éclat, 2007, 379 p. - Abécassis, Frédéric (Revue des mondes musulmans et de la Méditerranée, 2009)
Ce livre est le produit d’une rencontre, tenue à la Sorbonne en avril 2003, entre chercheurs français, tunisiens et israéliens à l’initiative de la Société d’histoire des Juifs de Tunisie. Le colloque s’est tenu sous le quadruple patronage de l’UNESCO, du CNRS, des ministères des Affaires étrangères et de l’Éducation nationale, en impliquant bien d’autres acteurs institutionnels. Sans qu’il n’y soit jamais fait référence, l’ouvrage, paru quatre ans plus tard, porte la marque du contexte dans ...
Keywords: Recension

PREVOST, Virginie, L'aventure ibadite dans le Sud tunisien (VIIIe-XIIIe siècle). Effervescence d'une région méconnue, Tuusula y Helsinki: Academia Scientiarum Fennica, "Humaniora 350", 2008, 479 págs., ilustraciones. - Viguerra Molins, Maria Jesus (Anaquel de Estudios Árabes, 2009)
Keywords: Recension

The Myth of the Sultans in the Western Indian Ocean during the Nineteenth Century: A New Hypothesis - Nicolini, Beatrice (African and Asian Studies, 2009)
Abstract The power of the Al Bu Sa'id Sultans of Oman was widely known as based on delicate balances of forces (and ethnic-social groups), deeply different among them. In fact, the elements that composed the nineteenth century Omani leadership were, and had always been, generally 'divided' amongst three different ethnic groups: the Baluch, the Asian merchant communities and the African regional leaders (Mwiny Mkuu). Within this framework, the role played by European Powers, particularly by the Treaties signed between the Sultans of Oman and the East India Company for abolishing slavery, and by the arms trade was crucial for the development of the Gulf and the Western Indian Ocean international networks They highly contributed to the gradual 'shifting' of the Omanis from the slave trade to clove and spice cultivation – the major economic source of Zanzibar Island – along the coastal area of Sub-Saharan East Africa. The role played by the Omani Sultans – the myth – within the western traditional historiography, which often described them as firmly controlling both the Arabian and African littorals and the major trading ports of the Western Indian Ocean during the nineteenth century, will be reexamined in this paper, taking into account recent research studies and international debates in the topic. The new hypothesis consists of a different perception of the concepts of power and control (political and territorial) of the Western Indian Ocean littorals by the most famous of the Sultans of Oman during the nineteenth century: Saiyid Sa'id bin Sultan Al Bu Sa'id.
Keywords: Zanzibar

'These Young Men Show No Respect for Local Customs'—Globalisation and Islamic Revival in Zanzibar - Turner, Simon (Journal of Religion in Africa, 2009)
Like elsewhere in Africa, local forms of Islam are being challenged by a number of new reformist and revivalist forms of Islam, influenced to some degree by a global Islamic revival but shaped by particular local histories and politics. This has caused some friction, especially as the regime in place seeks to manipulate these tensions for political benefit. Central to this struggle are the young men who have studied Islam abroad and who challenge the established truths of the traditional religious authorities; these authorities in turn accuse 'the youth' of bringing foreign, 'Arab' ideas and politics to Zanzibar. However, the kind of Islamic revival taking place in Zanzibar is far from radical or violent, and it is not appropriate to pose the present situation in terms of global Salafism versus local Sufism. In fact, Islamic revivalists often coin their critique of the state in terms of human rights and good governance and provide an alternative modernity that simultaneously challenges and articulates secular, liberal forms of modernity. Islamic revival critiques what is perceived as society's moral disorder and the state's inability to deal with new global challenges. Hence the present paper explores how global trends in Islam—but also global discourses on human rights and good governance—influence the current modes of Islamic revival in Zanzibar. With a heavily restricted political field, Islam can be a means of critiquing society without getting involved in politics. However, the government and the traditional religious authorities perceive this revivalism as a threat to the status quo and attempt therefore to politicise the struggle, accusing Islamic movements of fundamentalism and terrorism. It is within this political environment that Islamic revival must navigate.
Keywords: Zanzibar

Social and Intercultural Relations in Nineteenth-Century Zanzibar: Dressed Identity - Vander biesen, Ivan (African and Asian Studies, 2009)
Starting from the nineteenth century descriptive literatures on Zanzibar by authors such as Sir Richard Burton and Charles Guillain, and Salima bint Said-Ruete's autobiography, we can draw a rather detailed picture of the relationship between the different social layers, cultures and genders on Zanzibar. Describing and differentiating the complexity of Zanzibar society in the nineteenth century is the main aim of this paper. The focus is on clothing in order to sketch the social organization of the society and to highlight the cultural relations between the different groups in Zanzibar. The evidence obtained from the description of clothing is used as an eye-opener for the Zanzibar society and this evidence is supported by nineteenth century literature and photography on Zanzibar.
Keywords: Zanzibar

The Dido Episode in Ercilla's La Araucana and the Critique of Empire - Galperin, Karina; Wright, Elizabeth R. (Hispanic Review, 2009)
Keywords: Littérature -- Djerba

Effects of hydro-edaphic environment on the rooting of date palm (Phoenix dactylifera L.) Deglet Noor in the Ouargla Basin (south-east algeria) - Daddi-Bouhoun, Mustapha; Brinis, Louhichi; Saker, Mohamed-Lakhdar; Côte, Marc; Rabier, Jacques (Ecologia mediterranea, 2009)
Keywords: Botanique -- Ouargla

Source-Critical Methodologies in Recent Scholarship on the Khārijites - Gaiser, Adam R. (History Compass, 2009)
Keywords: Kharijisme

Insediamenti rupestri nel Gebel Nafusa occidentale (Libia) - Dell'Aquila, Franco; Bencini, Claudio; Fiorentino, Giuseppe (Opera Ipogea, 2009)
Si presenta un quadro degli aspetti ambientali del Gebel Nafusa libico ove sono presenti numerosi episodi di cavità artificiali scavate sia singolarmente sia in agglomerati come villaggi e città. Importanti sono i villaggi rupestri abbandonati perché
Keywords: Architecture -- Djebel Nefousa

Libya: Berber Town Beseiged (Africa Research Bulletin: Political, Social and Cultural Series, 2009)
Activists claim that the authorities on December 25th launched a security campaign against the Berber town of Yafran,170km south-west of Tripoli, the Saudi-owned pan-Arab daily Al-Sharq al-Awsat reported. Fathi Bin-Khalifah, coordinatorof the Libyan Action Group and the Lib-yan Amazighs’ Grouping, said in a tele-phone contact from his base in Moroccothat the Libyan authorities were besiegingthe town, electronically jamming telephonecontacts between it and the outside world,and also banning anyone coming fromother areas from entering. He claimed thatthere was intensive security deploymentafter units from the anti-riot Central Sup-port Forces were brought in and that hehad received information that military air-craft had flown over the town which has apopulation of around 50,000.According to assertions by Bin-Khalifahand various Amazigh (Berber) internetwebsites, groups from the ‘‘Youth Lea-gues’’ ofSayf-al-Islam, the second son ofLibyan Leader ColonelMouammar Gad-dafy, and elements from the Revolution-ary Committees attacked the capital ofJabal Nafusah and encircled and raidedthe houses of some known Amazigh fig-ures. Local residents said they did notknow the specific reason for the securitycampaign, while some sources said theLibyan authorities were punishing all theAmazighs because some of their leadershad taken part in an expanded recentconference held to discuss their condi-tions in the Maghreb.But Bin-Khalifah said ‘‘there is no direct orimmediate cause for these events’’ andnoted that the ‘‘International AmazighCongress’’, which adopts the Amazighs’causes from its base in France, had a meet-ing recently with Colonel Gaddafy andadded: ‘‘There are no signs or indications.What happened was sudden and there wereabsolutely no moves beforehand other thanthe regime’s attempt to get rid of thenatives and create a new pit of tension.’’Amazigh activists claim that their influenceand presence in Libyan social, profes-sional, economic, scientific, administrative,and military circles could have aroused thefears of the authorities towards thembecause of their opposition to any attemptto bequeath leadership of the nation toCol. Gaddafy’s son.Yafran with its Amazigh majority is thesecond Libyan town to witness suddentroubles following the violence thatoccurred a few weeks earlier in Al-Kufrahtown in the south of Libya between theLibyan authorities and the local citizens.They were demonstrating against their dete-riorating living conditions and the central authorities’ neglect of their rights to have official identity cards in addition to depriving their sons of the right to government education and other basic services.(Al-Sharq al-Awsat website 27⁄12: BBC Mon.)
Keywords: Vie politique -- Djebel Nefousa

Djerba et « los Gelves » - Buiza, Gonzola (El Legado andalusi : una nueva sociedad mediterranea, 2009)

Lagoonal sand smelts (atherina lagunaea, teleostei, atherinidae) inhabit marine shallow waters of the coasts of Djerba island (Tunisia) - Bouriga, Nawzet; Selmi, S.; Aurelle, D.; Barthelemy, R.; Quignard, Jean-Pierre; Trabelsi, M.; Faure, E. (Bulletin de l’Institut National des Sciences et Technologies de la Mer, 2009)
Keywords: Littoraux -- Djerba

Les analyses statistiques multivariées : application sur deux espèces de Soleidea des cotes Tunisiennes - Glid, A. (Bulletin de l’Institut National des Sciences et Technologies de la Mer, 2009)
Keywords: Botanique -- Djerba

Influence of socioeconomic lifestyle factors and genetic polymorphism on type 2 diabetes occurrences among Tunisian Arab and Berber groups of Djerba Island - Baroudi Ouederni, Thouraya; Fadiel, Ahmed; Stambouli, Nejla; Scalize, Trudy J; Ben Maiz, Hedi; Abid, Hafaona Kammoun; Bouhaha, Rym; Sanchez-Corona, Jose; Hamza, Adel; Benammar Elgaaied, Amel (Pharmacogenomics and Personalized Medicine, 2009)
Keywords: Génétique -- Djerba

Les mosquées ibadites du Maghreb - Prevost, Virginie (Revue des mondes musulmans et de la Méditerranée, 2009)
Keywords: Architecture -- Djerba; Bûlaymân, Mosquée (Ja’bîra, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Majlis, Mosquée al- (Guellala, Djerba); Monuments -- Djerba; Talâkin, Mosquée (Ghizen, Djerba); Tâjdît, Mosquée (Fâtû, Djerba)

Genetic diversity in local barley accessions collected from different geographical regions of Tunisia - Ould Med Mahmoud, M. A.; Hamza, S. (Plant Genetic Resources, 2009)
Keywords: Botanique -- Djerba

Nouvelle découverte dans la nécropole punique de Soûq el Guébli à Jerba - Ben Tahar, Sami (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 2009)
Keywords: Antiquité; Archéologie -- Djerba